THE FACTORS ASSOCIATE WITH THE INCIDENCE OF TYPE 2 DIABETES MELLITUS IN WOMEN IN THE WORKING AREA OF THE BIARO COMMUNITY HEALTH CENTER : TYPE 2 DIABETES MELLITUS - Azeny, Claudya Putri; Putri, Ade Suzana Eka; Widoyo, Ratno; Masrizal, Masrizal (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The global prevalence of type 2 diabetes mellitus is steadily increasing, with a particularly notable rise among women. This study aims to identify factors associated with type 2 diabetes mellitus among women in the working area of Biaro Public Health Center. Methods: A case-control study design was employed, involving 50 women diagnosed with type 2 diabetes mellitus (cases) and 50 women without type 2 diabetes mellitus (controls), selected randomly from the same population. Data were analyzed using both bivariate and multivariate statistical methods to determine significant predictors of type 2 diabetes mellitus. Results: Bivariate analysis revealed significant associations between type 2 diabetes mellitus with age, family history of diabetes, level of education, physical activity, and stress (p < 0.05). Multivariate analysis identified that low physical activity as the most influential risk factor. Conclusion: These findings highlight the urgent need for targeted health promotion strategies—particularly in the Biaro Public Health Center area— behavioral interventions such as physical activity on high-risk groups to effectively reduce the incidence of type 2 diabetes mellitus among women.